2016
DOI: 10.1016/j.jksus.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation: Potential flora for synthetic dyestuff metabolism

Abstract: Dumping of dye-laden effluents into different environmental compartments adversely affects equilibrium and integrity of ecological systems. Being genotoxic, mutagenic and carcinogenic these dyes are quite damaging to health of biota (either aquatic or terrestrial). Many of these dyes are resistant to degradation and remediation under natural conditions and through conventional treatment methods. This situation has necessitated the development of effective and efficient wastewater treatment strategies without f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(35 citation statements)
references
References 105 publications
0
32
0
3
Order By: Relevance
“…However, the outflow samples of unplanted ponds showed that the inflow peak at 1.693 min shifted to 1.736, 1.732 and 1.768 min for normal, high and low pH values, respectively. The presence of new peaks in the outflow samples as a result of new products indicates that the dye removal was due to phyto-transformation by plants (Khandare et al 2011) and bio-transformation by microbes (Tahir et al 2016).…”
Section: Outflow Water Quality Parameters (Phase 1)mentioning
confidence: 99%
“…However, the outflow samples of unplanted ponds showed that the inflow peak at 1.693 min shifted to 1.736, 1.732 and 1.768 min for normal, high and low pH values, respectively. The presence of new peaks in the outflow samples as a result of new products indicates that the dye removal was due to phyto-transformation by plants (Khandare et al 2011) and bio-transformation by microbes (Tahir et al 2016).…”
Section: Outflow Water Quality Parameters (Phase 1)mentioning
confidence: 99%
“…where C o and C t are dye concentration initially and after reaction time t (min), respectively.The reaction between dye molecules and nano iron particles was studied by varying nano iron dose (0.2, 0.4, 0.6, 0.8, 1.0, 1.2, and 1.5 g L −1 ), dye initial concentration (20,40,60,80, and 100 mg L −1 ), and dye initial pH (2,4,6,8,10). The pH of dye was adjusted using hydrochloric acid (1.0 mol L −1 ) or sodium hydroxide solution (1.0 mol L −1 ) and monitored using a digital pH meter.…”
Section: Dye Decolorization Experimentsmentioning
confidence: 99%
“…The systems are combining the physical, chemical and biological process to remove pollutant in wastewater. The main mechanisms involves in the treatment includes phytoaccumulation, phytodegradation, phytovolatilization, phytofiltration, rhizodegradation and phytodesalination [30].…”
Section: Mechanismmentioning
confidence: 99%
“…Suitable plant species used should have high uptake of both organic and inorganic pollutants, fast grow rate, tolerance in polluted water, adaptable to the climate and easily controlled in dispersion [31], [32]. In addition, the efficiency of phytoremediation treatment also depends on the plant species and their characteristics, interaction of their root zone, medium and wastewater properties and the environmental condition [30]. The key roles during implementation of phytoremediation are the rate of photosynthetic activity and the plant growth during the pollutant removal process [6].…”
Section: Aquatic Plantsmentioning
confidence: 99%